Effect of red mud addition on tetracycline and copper resistance genes and microbial community during the full scale swine manure composting. (September 2016) - Wang, Rui; Zhang, Junya; Sui, Qianwen; Wan, Hefeng; Tong, Juan; Chen, Meixue; Wei, Yuansong; Wei, Dongbin
Highlights: ARGs could be effectively removed through the thermophilic composting process. The main contributor of reducing ARGs abundance was pile temperature. Bacterial community was the main driver to reduction of ARGs abundance. Addition of red mud indeed hindered removal of ARGs during composting. Abstract: Swine manure has been considered as the reservoir of antibiotic resistance genes (ARGs). Composting is one of the most suitable technologies for treating livestock manures, and red mud was proved to have a positive effect on nitrogen conservation during composting. This study investigated the abundance of eight tetracycline and three copper resistance genes, the bacterial community during the full scale swine manure composting with or without addition of red mud. The results showed that ARGs in swine manure could be effectively removed through composting (reduced by 2.4 log copies/g TS), especially during the thermophilic phase (reduced by 1.5 log copies/g TS), which the main contributor might be temperature. Additionally, evolution of bacterial community could also have a great influence on ARGs. Although addition of red mud could enhance nitrogen conservation, it obviously hindered removal of ARGs (reduced by 1.7 log copies/g TS) and affected shaping of bacterial community during composting.